Reducing the Glucose Level in Pre-treatment Solution Improves Post-thaw Boar Sperm Quality - Zhu, Zhendong; Zhang, Weijing; Li, Rongnan; Zeng, Wenxian (Frontiers in Veterinary Science, 2022)
Frozen–thawed boar sperm was not widely used in pig artificial insemination as the sperm quality was damaged by biochemical and physical modifications during the cryopreservation process. The aim of this study was to investigate whether reduction of the glucose level in diluted medium could protect the post-thaw boar sperm or not. Boar sperm was diluted with the pre-treatment medium with different doses of glucose (153, 122.4, 91.8, 61.2, 30.6, and 0 mM) during the cooling process. The sperm motility patterns and glycolysis were evaluated during the cooling process. Meanwhile, the post-thaw sperm quality, ATP level, mitochondrial function as well as apoptosis were also measured. It was observed that 153 mM glucose treatment showed the highest glycolysis in boar sperm as the activities of hexokinase, fructose-bisphosphate aldolase A, and lactate dehydrogenase are the highest as well as the lactate level. Reduction of the glucose level from 153 to 30.6 mM suppressed sperm glycolysis. In addition, treatment with 153 mM glucose made the sperm demonstrate a circle-like movement along with a high value of curvilinear velocity and amplitude of the lateral head, while decreasing the glucose level reduced those patterns in the cooling process. Moreover, reduction of the glucose level also significantly increased the post-thaw sperm's total motility, progressive motility, straight-linear velocity, membrane integrity, and acrosome integrity. The treatment with 30.6 mM glucose showed the highest value among the treatments. Furthermore, the post-thaw sperm's succinate dehydrogenase activity, malate dehydrogenase activity, mitochondrial membrane potential as well as ATP level were increased by reducing the glucose level from 153 to 30.6 mM. Interestingly, the treatment with 30.6 mM glucose showed the lowest apoptosis of post-thaw sperm among the treatments. Those observations suggest that reduction of the glucose level in diluted medium increased the post-thaw boar sperm quality via decreasing the glycolytic metabolism. These findings provide novel insights that reduction of boar sperm activity via decreasing sperm glycolysis during the cooling process helps to improve the post-thaw sperm quality during cryopreservation.